Growth and exit of West German firms: an empirical investigation on the impact of liability statutes - Dietmar Harhoff; Konrad O. Stahl; Michael Woywode (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1995)
In this paper we discuss determinants of firm survival and growth in Germany within its pre-1989 boundaries. We develop our central hypotheses on the basis of a simple theoretical model describing the self-selection of heterogeneous entrepreneurs into particular legal forms, and the implications for profitability and survival. We also describe institutional details of liability regulation and taxation rules which German entrepreneurs face when choosing a particular legal form for their firms. We then test the predictions of our model by considering the survival chances and employment growth rates of various types of enterprises in a sample of approximately 11000 West German firms in all major sectors of the German economy. in our analysis of firm survival we distinguish between voluntary liquidation without losses to creditors, and bankruptcy as forced liquidation. Firms under limited liability are characterized by higher growth and higher insolvency rates than comparable firm under full liability. We also confirm the previously found negative relationship between employment growth and firm size which persists after controlling for selection biases. The likelihood of insolvencies is a nonmonotonic function of firm size.
Keywords: 330; Unternehmensentwicklung; Umwandlung; Unternehmenswachstum; Konkurs; Schuldrecht; Theorie; Deutschland